A Probabilistic Decision-Making Scoring System for Quality and Safety Management in Aloreña de Málaga Table Olive Processing - Ruiz Bellido, Miguel Á.; Valero, Antonio; Medina Pradas, Eduardo; Romero Gil, Verónica; Rodríguez-Gómez, Francisco; Posada-Izquierdo, Guiomar D.; Rincón, Francisco; Possas, Aricia; García-Gimeno, Rosa M.; Arroyo-López, Francisco N. (Frontiers in Microbiology, 2017)
Table olives are one of the most representatives and consumed fermented vegetables in Mediterranean countries. However, there is an evident lack of standardization of production processes and HACCP systems thus implying the need of establishing decision-making tools allowing their commercialization and shelf-life extension. The present work aims at developing a decision-making scoring system by means of a probabilistic assessment to standardize production process of Aloreña de Málaga table olives based on the identification of potential hazards or deficiencies in hygienic processes for the subsequent implementation of corrective measures. A total of 658 microbiological and physico-chemical data were collected over three consecutive olive campaigns (2014 – 2016) to measure the variability and relative importance of each elaboration step on total hygienic quality and product safety. Three representative companies were visited to collect samples from food-contact surfaces, olive fruits, brines, air environment, olive dressings, water tanks, and finished/packaged products. A probabilistic assessment was done based on the establishment of Performance Hygiene and Safety Scores (PHSS 0-100%) through a standardized system for evaluating product acceptability. The mean value of the global PHSS for the Aloreña de Málaga table olives processing (PHHSFTOT) was 64.82% (90th CI: 52.78- 76.39%) indicating the high variability among facilities in the evaluated processing steps on final product quality and safety. Washing and cracking, and selection and addition of olive dressings were detected as the most deficient ones in relation to PHSSFi values (p<0.05) (mean= 53.02 and 56.62% respectively). The relative contribution of each processing step was quantified by different experts (n=25) from the Aloreña de Málaga table olive sector through a weighted PHSS (PHSSw). The mean value of PHSSw was 65.53% (90th CI: 53.12 – 77.52%). The final processing steps obtained higher values for PHSSw being the finished product the most relevant one (mean= 18.44%; 90% CI: 10.34 – 25.33%). Sensitivity analysis concluded that intervention measures focused on reducing the contamination of washing brines could lead to an improvement of PHSSFTOT value to 67.03 %. The present work can be potentially applied in the Aloreña de Málaga table olive food sector for improving food quality and safety assurance.